Global colorectal cancer research, 2007‐2021: Outputs and funding. Issue 3 (28th September 2022) - Begum, Mursheda; Lewison, Grant; Wang, Xiang; Dunne, Philip D.; Maughan, Tim; Sullivan, Richard; Lawler, Mark
Abstract: The purpose of this study was to provide an evidence base for colorectal cancer research activity that might influence policy, mainly at the national level. Improvements in healthcare delivery have lengthened life expectancy, but within a situation of increased cancer incidence. The disease burden of CRC has risen significantly, particularly in Africa, Asia and Latin America. Research is key to its control and reduction, but few studies have delineated the volume and funding of global research on CRC. We identified research papers in the Web of Science (WoS) from 2007 to 2021, and determined the contributions of the leading countries, the research domains studied, and their sources of funding. We identified 62 716 papers, representing 5.7% of all cancer papers. This percentage was somewhat disproportionate to the disease burden (7.7% in 2015), especially in Eastern Europe. International collaboration increased over the time period in almost all countries except in China. Genetics, surgery and prognosis were the leading research domains. However, research on palliative care and quality‐of‐life in CRC was lacking. In Western Europe, the main funding source was the charity sector, particularly in the UK, but in most other countries government played the leading role, especially in China and the USA. There was little support from industry. Several Asian countries provided minimal contestable funding, which may have reduced the impact of their CRC research. Certain countries must perform more CRC research overall, especially in domains such as screening, palliative care and quality‐of‐life. The private‐non‐profit sector should be an alternative source of support. Abstract : What's new? Active research is key to high‐quality colorectal cancer (CRC) care. Here, the authors catalogued CRC research published between 2007 and 2021 with regard to study topics, funding, and the relative contribution of different countries. CRC accounted for 5.7% of all cancer papers, slightly less than its share of the disease burden. Some regions, such as Eastern Europe, are underperforming in CRC research relative to their economic status. Leading areas of research included genetics and surgery, and more research is needed on palliative care and quality‐of‐life. Some countries, including China and the US, provide substantial government funding for CRC research, while others rely on the charity sector. Overall, the private sector provided little funding.